Constitutional Law in Action and the Capabilities Approach to Development: Lessons From Peru, Israel an Australia - Scnweber, Howard (Право и государство, 2013)
This article asks us to consider the relationship between constitutional law and social development in terms of two particular ways of thinking. First, the article proposes that social and economic development should be thought about in terms of the «capabilities approach» that measures «development» in terms of the expansion of opportunities for individuals in the society to realize their potentials. Second, the article asks us to think about constitutional law in terms of «law in action», meaning the way law works in social and economic practice to structure relationships. Constitutional law in action describes the way constitutional legal arguments and categories of thinking affect social and economic development. The question being addressed can therefore be phrased as «what can we learn from looking at foreign examples about the role of constitutional-law-in-action in furthering citizens’ capabilities and opportunities for self-realization?». Drawing on examples from Peru, Israel, and Australia, the article argues that constitutional law in action is a critical element in the development of capabilities, and needs to be a primary focus for any nation that attempts to pursue the goal of social modernization.
Keywords: constitution; development; capabilities; comparative politics; society; modernization; democratization; Research Subject Categories::LAW/JURISPRUDENCE